Finite element analysis of knee and ankle joint during gait based on motion analysis. (January 2019) - Park, Sangbaek; Lee, Seungju; Yoon, Jeongro; Chae, Soo-Won
Highlights: A new method that integrates FE analysis with rigid body dynamic analysis is proposed. Interface program with self-written codes is developed to apply the results of motion analysis to the FE analysis. Coordinate system matching OpenSim model and FE model is performed to transform the FE model. Contact pressure distribution at the knee and ankle joints can be obtained according to the desired stance phase. Abstract: Contact pressures in the articular cartilage during gait affect injuries and the degenerative arthritis of knee and ankle joints. However, only contact forces at the knee and ankle joints during gait can be estimated by using a rigid body dynamic model. The contact pressure distribution can be obtained quantitatively for a static posture by using finite element (FE) analysis in most cases. The purpose of this study is to develop a new method to obtain the contact pressure distribution at the knee and ankle joints during gait by integrating FE analysis with rigid body dynamic analysis. In this method, a reference FE model of the lower extremity is constructed first and is then transformed to each stance phase of the gait obtained from dynamic analysis by using homogeneous transformation. The muscle forces and ground reaction force (GRF) during gait obtained from the dynamic analysis were used as loading conditions for FE analysis. Finally, the contact pressure distribution at the tibia plateau cartilage and talus cartilage were estimated at the 1st peak, mid-stance, and the 2nd peak at the same time. The present method can provide the contact pressure distribution at the knee and ankle joints over the entire gait.